Extraluminal hypopharyngeal foreign body - Vadhera, Raman (Springer-Verlag, 2009)
Ingestion of a foreign body is a problem seen in nearly all otolaryngologic practices. Ingested foreign bodies which migrate extraluminally are rare occurrences. If untreated, they may result in life threatening complications. We are reporting a case of sharp metallic pin which migrated extraluminally in the hypopharynx and became lodged in the soft tissue. It was successfully removed by direct laryngoscopy.